THE RELATIONSHIP BETWEEN KNOWLEDGE AND NURSES ATTITUDE TOWARDS THE IMPLEMENTATION OF PERMANENT PROCEDURES IN INFUSION INSTALATION - Parliastina, Dili; Muhyiddin, Zeni; Dahlia, Dwi (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Hospital and other health service facility must implement the prevention and control of infection (PPI) in accordance with the Decree of the Minister No 270/MINISTER/2007. However, in 2010, at Lung Hospital âDr. H. A. Rotinsulu Bandungâ, Indonesia, among 868 patients who had the infusion, the incidence rate of phlebitis reached to 2.64 %. In the infusion installation management, nurses must have knowledge, skills and adequate attitude toward the procedure. Aims: This study aims to assess how nursesâ knowledge to the infusion procedure affects their attitude. Method: It was a descriptive study using a cross sectional approach. A total of 70 nurses from lung hospital âDr. H. A. Rotinsulu Bandungâ, Indonesia, was selected using random sampling technique from April to July 2011. The nurses work in hospital ward, intensive care unit and emergensy instalation. The respondents were given questionnaire regarding to the assessment of nursesâ knowledge and attitude. The collected data was analyzed using Person test to show the association between nursesâ attitude and their knowledge to the infusion procedure. Results: Most of respondents (57.1%) work for 11-20 years. While 38.6% nurses employ less than 10 years, there were 14.3% nurses work for more than 21 years. However, as shown in Table 3, out of 70 nurses, only 50% have good knowledge to the infusion procedure, while 32.9% nurses have enough understanding. The rest 17.1% need more attention, where 2 of that 12 nurses orchestrated negative attitude to the procedure. In addition, the statistical analysis shows that the relationship between the knowledge and the attitude of nurses about infusion procedures was found significant (p value = 0.002). Conclusion: The results shows the length of work will not affect to the better knowledge of nurses to the infusion procedures. The negative attitude that found among the nurses indicated the importance to highlight this issue to the hospital management. Attention to their understanding to the infusion procedure will improve their attitude, in return it can prevent accident during the handling.Â